Dynamical Analysis of HIV/AIDS Epidemic Model with Treatment - Ulfa, Badria; Trisilowati, Trisilowati; K., Wuryansari M. (The Journal of Experimental Life Science, 2018)
In this article, an epidemic model of HIV/AIDS with treatment is observed. This model consists of five populations: susceptible, educated susceptible, exposed, HIV infected, and AIDS infected. Antiretroviral therapy (ART) is one type of treatment that can be given to individual that is infected by HIV. This medication can prevent the growth of the virus. Exposed individuals are given short-term antiretroviral treatment called Post Exposure Prophylaxis (PPP), while for infected individuals are given treatment by combining two or three types of antiretroviral drugs. Dynamical analysis is performed by determining equilibrium points and local stability analysis. Based on the analysis results, two equilibrium points are obtained, namely disease-free equilibrium point and endemic equilibrium points. The stability analysis shows that the free equilibrium point is locally asymptotically stable if R0 < 1 and the endemic equilibrium point is locally asymptotically stable under certain conditions. Numerical simulations show that giving two medications together has a greater effect in reducing the spread of the disease. Keywords: antiretroviral, dynamical analysis, HIV/AIDS.